DESIGN OF A MINI WIND POWER PLANT USING A WASHING MACHINE DYNAMO AS A Crate ENERGY SOURCE COOLING FISH ON SHIP TRADITIONAL FISHERMAN - Maulana Ifdil Hanafi; Suwasti Broto; Eka Purwa Laksana (MAESTRO, 2023)
Electricity is an important need for the people of Indonesia, but the need for electricity on traditional fishing boats is one of the main causes because traditional fishing boats do not have po wer plants as a source of energy for refrigerators and also for lighting on traditional fishing boats. Based on these problems, a mini wind power plant was created as a renewable energy using an AC Servo Motor as a generator, and a rectifier as a voltage r ectifier, SCC (Solar Charge Controller) as input and output control, and Arduino Uno as a microcontroller, which works with utilizing sea breeze pressure of 13,73 m/s, with RPM on the rotor of the ac servo motor of 225, and producing a voltage value of 14, 51 VDC, a current value of 12 ,2 mA, and a power of 177 , 022 mW. Later the voltage generated by the PLTB (Wind Power Plant) will be used as an energy source for charging the battery with a charging time of 15 minutes per 0 , 1 VDC, and using the battery as a source of cold storage energy for 6 hours with the lowest temperature at colg storage of 6,7 °c.